Caracterização e avaliação do potencial da quitosana extraída de cunninghamella elegans na formação de cristais de oxalato de cálcio e atividade antioxidante - Souza Neto, Francisco Ernesto de (2017)
With the advent of technology in the world, the emergence of a variety of materials had and has its defining role within society. This allows other materials, in addition to the existing classics, to fill some gaps necessary to meet human needs, such as biomaterials. The characteristics of biomaterials such as biocompatibility and low toxicity give them the ability to use biomedical devices that can be used in contact with biological systems. One of the biomaterials being used in large scale in the biomedical area is chitosan. Chitosan is a derivative of the chitin deacetylation process, and is referred to as a β-1,4-D-glucosamine linear chain polymer, bound to N-acetyl-D-glucosamine residues, which in turn has a helical three-dimensional configuration stabilized between molecules by hydrogen bonds. After the solution of chitosan ready, FT-IR, XRD and molecular weight analyzes of fungi and animal chitosan were analyzed, as well as analysis of antioxidant activities in vitro, the formation of Oxalate of Calcium (OxCa), including zeta potential, and the cytotoxicity tests of fungal chitosan on HEK renal cells. It was possible to determine a fungal chitosan with degree of deacetylation of 76% and low molecular weight. This in turn presented less phenolic compounds than animal chitosan, in addition to both presented low total antioxidant activity, as well as low iron chelating activity and a chelating activity of copper around 70%. In the OxCa formation assay, it was possible to detect a decrease in number, and an increase in the size of the crystals, in the comparison of the presence of fungal chitosan in relation to animal chitosan. The results of cytotoxicity tests showed fungal chitosan that allowed viability around 70% of healthy renal cells in three of the five concentrations tested. In view of the above, fungal chitosan has the capacity to continue being a biomaterial of great importance for the new generation of materials in use in health